Codemeshing or Linguistic Purity: A Case Study of Wechat Languaging among Youngsters - Gu, Nancy (Technium Social Sciences Journal, 2021)
What are the specific manifestations of the codemeshing? In Wechat, how is this performance further reflected? What is the modality frequently used by youngsters? What are the characteristics of this modality and how do they realize? How do youngsters treat language? These seemingly simple questions are actually a profound discussion of social and cultural phenomena. This study seeks to solve these problems. The case in this research comes from a group of 23-27-year-old postgraduates of English major, taking the currently widely used social media—WeChat as the research platform, using case studies as research method, and Vygotsky’s Social and Cultural Theory as well as the Visual Grammar under the multi-modal analysis framework as the theoretical support, with a combination of quantitative and qualitative analysis, tries to analyze codemeshing discourse, and conclude with the youngsters’ attitude towards language to explore language development issues.